2010
DOI: 10.1155/2010/804298
|View full text |Cite
|
Sign up to set email alerts
|

The Traditional Japanese Formula Keishibukuryogan Inhibits the Production of Inflammatory Cytokines by Dermal Endothelial Cells

Abstract: Keishibukuryogan (KBG) is one of the traditional herbal formulations widely administered to patients with blood stagnation for improving blood circulation; currently, it is the most frequently prescribed medicine in Japan. KBG has been reported to improve conjunctional microcirculation. The aim of this study was to evaluate the role of KBG and paeoniflorin, a bioactive compound of KBG, in inhibiting the production of inflammatory cytokines using human dermal microvessel endothelial cells (HDMECs). The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In the present study, LPS challenge markedly elevated the formation of NO and iNOS expression in mouse lung tissues. PF markedly suppressed the expressions of iNOS mRNA in lung tissues and decreased the levels of NO in BALF, which was consistent with previous findings that PF could decrease iNOS expression in LPS-stimulated human dermal microvascular endothelial cells and in ear tissues of contact dermatitis mice [37,38]. Taken together, the protection afforded by PF against LPS-induced ALI in mice is related to inhibition of proinflammatory cytokine production in lung tissues.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, LPS challenge markedly elevated the formation of NO and iNOS expression in mouse lung tissues. PF markedly suppressed the expressions of iNOS mRNA in lung tissues and decreased the levels of NO in BALF, which was consistent with previous findings that PF could decrease iNOS expression in LPS-stimulated human dermal microvascular endothelial cells and in ear tissues of contact dermatitis mice [37,38]. Taken together, the protection afforded by PF against LPS-induced ALI in mice is related to inhibition of proinflammatory cytokine production in lung tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, it was also the most frequently prescribed herbal formula to treat endometriosis (Fang et al, 2012). Regarding the mechanistic studies, it was found to inhibit the activity of estrogen metabolism-related cytochrome P450 1A2 (CYP1A2) (Saruwatari et al, 2012), decrease the activity of inducible nitric oxide synthase (iNOS) and endothelial nitric oxide synthase (eNOS) (Nozaki et al, 2007;Yoshihisa et al, 2010). It is noteworthy that iNOS and eNOS were highly expressed in uterine fibroid tissue, and related to menorrhagia, dysmenorrhea and the development of uterine fibroid (Gokdeniz et al, 2000;Oh et al, 2013;Plewka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These medicinal plants were boiled and the extracts cooled to room temperature and stored at 4°C. Furthermore, the extracts were individually suspended in RPMI 1640 (SigmaAldrich Co., STL, USA ) medium containing 10% foetal bovine serum (Gibco Co., Grand Island, NY, USA) and 1% streptomycin (Sigma-Aldrieh Co.) and were rotated at 4°C overnight (7). The suspension was centrifuged and the supernatant filtered through a 0.45 |j.m-pore membrane, as described previously (7).…”
Section: Methodsmentioning
confidence: 99%